Perbandingan Efek Pemberian Kopi Robusta Lampung dengan Kopi Arabika Lampung Terhadap Gambaran Histologi Lambung Tikus Putih (Rattus Norvegicus) Jantan Galur Sprague Dawley - Rosbhaiti Chodijah; Susianti, Susianti; Ayu Tiara Fitri; Indri Windarti (Pusat Riset dan Inovasi Nasional, 2026)
Glycated hemoglobin (HbA1c) is a key marker for evaluating long-term glycemic control and has increasingly been studied for its potential association with various gastric disorders. Chronic hyperglycemia can impair gastric mucosal integrity through mechanisms involving oxidative stress, epithelial dysfunction, and inflammation, contributing to conditions such as gastritis, mucosal atrophy, and even precancerous lesions. This review summarizes research from the last ten years that investigated the relationship between HbA1c levels and different gastric conditions, using full-text, freely accessible observational, cohort, and experimental studies focused on metabolic regulation and mucosal changes. Current findings indicate that higher HbA1c levels are frequently associated with increased mucosal inflammation, a greater incidence of atrophic alterations, and a higher likelihood of premalignant or malignant gastric changes. Several studies also suggest that metabolic imbalance may worsen gastric function by enhancing oxidative stress and sustaining chronic inflammatory responses. Variability in comorbidities, metabolic factors, and additional gastrointestinal influences likely contributes to these inconsistencies. Overall, existing evidence suggests a meaningful yet variable link between glycemic status and gastric pathology. More standardized, well-controlled investigations are needed to clarify causal pathways and to refine clinical assessment strategies for individuals with metabolic or gastric disorders